2010
DOI: 10.21608/jhiph.2010.20607
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes among Medical Laboratories Staff Occupationally Exposed to Formaldehyde Vapors

Abstract: Background: Increased levels of tumour markers: carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC-Ag), Alpha feto protein (AFP), and neuron-specific enolase (NSE) may indicate the onset of the carcinogenic process. The aminotransferases, alanine aminotransferase (ALT) and aspartate aminotransferase (AST), are the most commonly measured enzymes that detect hepatocellular injury. Formaldehyde has an important application as a disinfectant and preservative, reason why relevant workplace exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on the study by Khalid Al-Saeed, the other factors in analyzing the blood coagulation time, i.e., the PT, in the exposed group to vibration had an increase, as compared to the control group. [2] The aPTT was analyzed in the current study, and the increase in it was observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the study by Khalid Al-Saeed, the other factors in analyzing the blood coagulation time, i.e., the PT, in the exposed group to vibration had an increase, as compared to the control group. [2] The aPTT was analyzed in the current study, and the increase in it was observed.…”
Section: Discussionmentioning
confidence: 96%
“…[1] Exposure to both types of occupational vibrations ends up in improper effects on musculoskeletal, cardiovascular and nervous systems, blood biochemical condition, and physiological as well as psychological aspects. [2] Human reaction to vibrations depends on the amplitude, frequency, and exposure time of vibration and the sensitivity of tissue. [3] Human exposure to hand–arm vibration has extensive complications.…”
Section: Introductionmentioning
confidence: 99%